2018
DOI: 10.1111/1477-9552.12275
|View full text |Cite
|
Sign up to set email alerts
|

Tenure Security and Farm Efficiency Analysis Correcting for Biases from Observed and Unobserved Variables: Evidence from Benin

Abstract: We analyse the impact of land tenure security on the technical efficiency of a sample of smallholder farmers in Benin, based on an output‐oriented stochastic distance function. We use propensity score matching to correct for selection bias from observed variables. The Greene () sample selection model is used to correct for selection bias due to unobserved variables. We estimate meta‐frontiers to analyse agricultural productivity and efficiency differences between landowners and non‐owners. Our results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 50 publications
(97 reference statements)
2
35
1
Order By: Relevance
“…Simply put, there is a likelihood that the error component in the selection equation is correlated with the conventional random error in the SPF, resulting to possible self-selection bias, which has to be tackled in order to obtain consistent and unbiased parameter estimates of the causal impact of cooperative membership. To address this estimation issue, we adopt a multi-step procedure as employed in previous studies by Bravo-Ureta et al [ 58 ], González-Flores et al [ 37 ], Villano et al [ 52 ], Lawin and Tamini [ 48 ], Ma et al [ 16 ], and Abdul-Rahaman and Abdulai [ 18 ]. The first stage involves the application of the propensity score matching (PSM) to correct for the selection bias due to observable attributes.…”
Section: Conceptual Framework and Estimation Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Simply put, there is a likelihood that the error component in the selection equation is correlated with the conventional random error in the SPF, resulting to possible self-selection bias, which has to be tackled in order to obtain consistent and unbiased parameter estimates of the causal impact of cooperative membership. To address this estimation issue, we adopt a multi-step procedure as employed in previous studies by Bravo-Ureta et al [ 58 ], González-Flores et al [ 37 ], Villano et al [ 52 ], Lawin and Tamini [ 48 ], Ma et al [ 16 ], and Abdul-Rahaman and Abdulai [ 18 ]. The first stage involves the application of the propensity score matching (PSM) to correct for the selection bias due to observable attributes.…”
Section: Conceptual Framework and Estimation Strategymentioning
confidence: 99%
“…The parameter ρ denotes the absence or presence of selectivity bias. If ρ is significant, it implies the presence of selection bias stemming from unobserved factors [ 48 , 52 ]. The estimation of the parameters in the model is based on the traditional gradient-based Broyden-Fletcher-Goldfarb-Shanno (BFGS) technique, while the Berndt-Hall-Hall-Hausman (BHHH) algorithm estimator was used to obtain asymptotic standard errors [Greene [ 22 ] contains details regarding structure and estimation of the model].…”
Section: Conceptual Framework and Estimation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions, land rights were not found to be a significant factor in determining whether or not farmers made land-improving investments, used yield-enhancing inputs, accessed credit, or improved the productivity of land. A study that included Ghana, Kenya and Rwanda, found 'no relationship between cross-sectional variations in land rights and productivity' [50]. The authors argue that the most pronounced relationships were found in Rwanda, where the right to bequeath was a significant determinant of some types of land improvements.…”
Section: Evidence For Relations Between Land Registration and Agriculmentioning
confidence: 97%
“…Related studies have been done by González‐Flores et al (2014) using data from small‐scale potato farmers in Ecuador, and Villano et al (2015) analyzing the impact of certified rice seed varieties in the Philippines. More recently, De los Santos‐Montero and Bravo‐Ureta (2017) examined the productivity effects of a natural resource management program implemented in Nicaragua; Abdulai and Abdulai (2017) assessed the impact of conservation practices on the environmental efficiency of maize producers in Zambia; Abdul‐Rahaman and Abdulai (2018) studied the impact of farmer groups on yields and TE in Northern Ghana; Aravindakshan et al (2018) analyzed the TE of conservation tillage for wheat farming in South Asia; and Lawin and Tamini (2019) measured the impact of land tenure security on TE in Benin.…”
Section: Impact Evaluation and Stochastic Frontiersmentioning
confidence: 99%